2018
DOI: 10.1136/bmjspcare-2018-001519
|View full text |Cite
|
Sign up to set email alerts
|

What is the cost of palliative care in the UK? A systematic review

Abstract: The data are limited, and the heterogeneity is such that it is not possible to provide an aggregate cost of palliative care in the UK. It is notable that the costs of hospice care and informal care are often neglected in economic studies. Further work is needed to address methodological and practical challenges in order to gain a more complete understanding of the costs of palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
0
29
0
1
Order By: Relevance
“…Palliative care clinicians also report that they have limited access to referring patients to psychological services [11]. Moreover, with increasing pressure on service funding, there is an even greater need for evidence of intervention benefit [12].…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care clinicians also report that they have limited access to referring patients to psychological services [11]. Moreover, with increasing pressure on service funding, there is an even greater need for evidence of intervention benefit [12].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review on the costs of palliative care in the UK highlighted the variation in estimates in different studies [9]. Our study found that costs for PCDS also vary across centres and across the UK, with differences in staff mix, volunteer mix and attendance rates all identified as elements of this variation.…”
Section: Discussionmentioning
confidence: 63%
“…Despite the growth of PCDS over the past 20 years in the UK, evidence of their costs and effects is limited. Where there is evidence, it has been collected in London and the South East of England in the main, and there is considerable variation in cost estimates for many types of palliative care services [9]. For example, a study conducted in 1999 involving five centres in Southern England found that PCDS cost around £79 (2018 value) per person per day, rising to £109 (2018 value) if unfunded resources (volunteer time) were included [10].…”
Section: Introductionmentioning
confidence: 99%
“…The role of donations in the provision of HPC services depends on the health care systems in different nations. In the United Kingdom, a third of the funding for hospice care services comes from the National Health Service, while the rest comes from charitable donations . In Singapore, hospice care services are mainly funded by charities under a combined public and private health care system.…”
Section: Discussionmentioning
confidence: 99%